The Use of Kirchhof Chemical Index to Determine the Quality of the Siak River’s Water - Ritonga, Rahmi Monalisa; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Siak river is one of the most polluted river in Riau. To understand the water quality in general, a research on the water quality of the river based on Kirchhof Chemical Index was conducted from December 2015 to February 2016. There were four stations. In each station water samples were collected from 3 sites, 3 times, once/week. Water quality parameters measured were temperature, conductivity, transparency, pH, dissolved oxygen, BOD5, ammoniac, nitrate, and phosphate concentration. Results shown that water quality in the research area are as follows : temperature 28.94-29.51°C, transparency 35.06-37.04 cm, depth 8.57-12.75 m, conductivity 55.43-58.87μS/cm, pH 5, dissolved oxygen 2.13-2.28 mg/L, BOD5 7.43-12.14 mg/L, ammoniac 0.50-0.75 mg/L, nitrate 0.58-0.78 mg/L and phosphate 0.07-0.22 mg/L. The value ofthe Kirchhof Chemical index was 23.80-31.19, indicates that this river is medium to highly polluted.Keywords : Siak River, Water Quality, Kirchhof Chemical Index